2018
DOI: 10.1016/j.aju.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in male infertility: An updated review of literature

Abstract: ObjectivesTo review the literature and provide an updated summary on the role of reactive oxygen species (ROS) in male infertility.MethodsA review of PubMed, Cochrane review, and Web of Science databases for full-text English-language articles published between 1943 and 2017 was performed, focusing on the aetiology of ROS, physiological role of ROS on spermatic function, pathological role of ROS in infertility, evaluation of ROS, and role of antioxidants in oxidative stress.ResultsROS play a role in spermatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
239
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(254 citation statements)
references
References 52 publications
6
239
0
9
Order By: Relevance
“…[44] Enzymatic antioxidants prevent infertility via scavenging of superoxide anions, protection against lipid peroxidation and DNA damage as well as increased sperm motility. [43] In this study, the administration of scopolamine caused a reduction in GST activity. Caffeine and donepezil increased GST activity in scopolamine-induced rats.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…[44] Enzymatic antioxidants prevent infertility via scavenging of superoxide anions, protection against lipid peroxidation and DNA damage as well as increased sperm motility. [43] In this study, the administration of scopolamine caused a reduction in GST activity. Caffeine and donepezil increased GST activity in scopolamine-induced rats.…”
Section: Discussionmentioning
confidence: 62%
“…High levels of ROS and MDA in sperm cells promotes mitochondrial dysfunction, DNA fragmentation as well as high caspase activities and cell death. [43] Treatment with caffeine and donepezil attenuated radical-induced testicular and epididymal tissue damage as revealed by the decrease in ROS and MDA levels in these tissues. The mechanism by which caffeine and donepezil protects rats' testis and epididymis against oxidative damage could be due to their capacity to mitigate scopolamine-induced cognitive dysfunction which reduces the generation of free radicals and attacks on lipid membrane.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although C. elegans is a well-established organism for studying aging and reproduction, with several studies describing hermaphrodite reproductive senescence, many questions regarding the basis of male reproductive decline remain unanswered. Decades of work have shown that exposure to pollution, toxins, xenobiotics, and other ROS-inducing compounds can prematurely drive the loss of sperm function across species (Agarwal, Virk, Ong, & du Plessis; Cocuzza, Sikka, Athayde, & Agarwal; Wagner, Cheng, & Ko), but the impact that normal cellular metabolism plays on sperm function and the identification of specific molecules that can mediate sperm quality are not well-defined. In this study we characterized a new role for mitochondrial proline catabolism and FAD homeostasis in the maintenance of proper sperm function.…”
Section: Discussionmentioning
confidence: 99%
“…Registration of a large number of morphologically abnormal sperm heads indicates an increased mutation process in male germ cells, particularly an increased frequency of gene mutations and/or microdeletions in spermatogonia and first-range spermatocytes (Enciso et al, 2011). According to several studies, a sudden increase in the frequency of chromosome mutations is caused by disorders in the repair of DNA fragments and in the antioxidation system (Zakhidov et al, 2001;Evdokimov et al, 2006;Wagner et al, 2018).…”
mentioning
confidence: 99%